Manuscript of Ali Chernavi / copy of the National Library in Paris - 762 Turks - Hussein , Dr. Shaima Jassem (Thi Qar Arts Journal, 2023)
The National Library in Paris abounds with a large number of manuscripts decorated with miniatures, which varied between literary, religious, scientific and historical manuscripts. They were written in the three languages Arabic, Persian and Turkish. Among those manuscripts is a copy decorated with illustrations from the famous poetic divan "Diwan Ali Shirnawi" by the Prince of Poets Ali Shirnawi. This study attempts to identify the artistic methods and pictorial characteristics that were used in the miniatures of this copy of the above manuscript